The Use of Conceptual Metaphor in The Lyrics of “Transform” by Daniel Caesar - Permadi, Erril Haerul; Prihandini, Asih (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2026)
This study investigates the deployment of conceptual metaphors within the lyrical framework of “Transform by Daniel Caesar, employing Lakoff and Johnson’s Conceptual Metaphor Theory (CMT) as its analytical foundation. Through descriptive qualitative methodology, five conceptual metaphors were systematically identified and interpreted, encompassing structural metaphors that map the self onto predatory animals, an ontological metaphor elevating the speaker to divine status, a nature-based metaphor attributing floral imagery to the beloved, and a soteriological metaphor positioning the beloved as a redemptive figure. The findings demonstrate that these metaphors operate as an interconnected cognitive system rather isolated linguistic units, collectively constructing a progressive existential narrative of self-transformation. Keywords: Conceptual Metaphor, Song Lyrics, Cognitive Linguistics